TI_GERICHTE 52.2020.109 vom 22. Januar 2020 , Ammonimento per infrazione alle norme dalla circolazione (eccesso di velocità) - TI Tribunale d'appello (2020)
Ammonimento per infrazione alle norme dalla circolazione (eccesso di velocità)